Educational technologies used in health education for people with deafness: An integrative review (Research, Society and Development, 2021)
The difficulty of communication in the deaf individual has serious consequences given the obstacles faced to acquire information about health education. However, technologies can collaborate with access to knowledge for health promotion and disease prevention. Thus, the aim of this study is to identify scientific evidence found in the literature about educational technologies in the field of health for the deaf. It is an integrative literature review, carried out in six stages, in which the articles were selected in Portuguese, English and Spanish in the databases: Medline via Pubmed, Latin American and Caribbean Literature in Health Sciences, Cochrane Library and Web Of Science. The articles were organized by year of publication. The final sample resulted in 10 articles, published between 2010 and 2020, with levels of evidence II, III and IV. In the identification of the technological resources observed, educational videos deserve to be highlighted, used in four (40%) publications, followed by evaluations in the use of health sites, SMS, application and online courses. With that, it was verified the effectiveness of assistive technologies, which contribute to equal access, quality of life and educational support for the promotion of the health of the public.